Effect of shadenet color and its intensity on tomato crop performance - Ramana Rao, KV; Gangwar, Suchi; Aherwar, Pushplata (Emirates Journal of Food and Agriculture, 2023)
At the research farm of Central Institute of Agricultural Engineering, Bhopal, India experimental trials were conducted during three rainy seasons (June-October) starting with 2016-2017. In this study red, white, black and green colors shade nets with varying shade intensities (35, 50 and 75 %) were studied by constructing each shadenet of 100 m2 size. All the tomato crop growth parameters significantly varied with shade net colours and intensities. Crop under red coloured shadenet house was found to have highest plant height and more branches over crop cultivation in other coloured net houses. Among the shade intensifies crop under 50% had highest plant height and more branches per plant as compared to crop under other intensities. Tomato crop under 50% shade intensity with red color shade net gave highest yield and the lowest yield was observed in 75% green colured shadenet house. Reduction in average ambient temperatures over control (outside the shadenet house, which was 30oC) in different shadenets are 3.2-5.9 0C under black shade net, 1.4-3.5 0C under green, 3.0 -5.3 0C under white, 2.0 – 4.4 0C under red coloured shade net house Average light intensity under ambient conditions was highest with 1,10,000 lux whereas in shade net houses the light intensities are much lower than the ambient conditions. The light intensities were found to be highest in green coloured net house for all intensities followed by red, white and black coloured net houses